Rethinking RFID: awareness and control for interaction with RFID systems - Marquardt, Nicolai; Taylor, Alex; Villar, Nicolas; Greenberg, Saul (Proceedings of the 28th international conference on Human factors in computing systems, 2010)
People now routinely carry radio frequency identification (RFID) tags - in passports, driver's licenses, credit cards, and other identifying cards - from which nearby RFID readers can access privacy-sensitive information. The problem is that people are often unaware of security and privacy risks associated with RFID, likely because the technology remains largely invisible and uncontrollable for the individual. To mitigate this problem, we introduce a collection of novel yet simple and inexpensive tag designs. Our tags provide reader awareness, where people get visual, audible, or tactile feedback as tags come into the range of RFID readers. Our tags also provide information control, where people can allow or disallow access to the information stored on the tag by how they touch, orient, move, press or illuminate the tag.